Composite particles formed by complexation of poly(methacrylic acid) - stabilized magnetic fluid with chitosan: Magnetic material for bioapplications - Safarik, Ivo; Stepanek, Miroslav; Uchman, Mariusz; Slouf, Miroslav; Baldikova, Eva; Nydlova, Leona; Pospiskova, Kristyna; Safarikova, Mirka (Materials science & engineering. C, Materials for biological applications, 2016)
A simple procedure for the synthesis of magnetic fluid (ferrofluid) stabilized by poly(methacrylic acid) has been developed. This ferrofluid was used to prepare a novel type of magnetically responsive chitosan-based composite material. Both ferrofluid and magnetic chitosan composite were characterized by a combination of microscopy (optical microscopy, TEM, SEM), scattering (static and dynamic light scattering, SANS) and spectroscopy (FTIR) techniques. Magnetic chitosan was found to be a perspective material for various bioapplications, especially as a magnetic carrier for immobilization of enzymes and cells. Lipase from Candida rugosa was covalently attached after cross-linking and activation of chitosan using glutaraldehyde. Baker's yeast cells (Saccharomyces cerevisiae) were incorporated into the chitosan composite during its preparation; both biocatalysts were active after reaction with appropriate substrates.
Keywords: kyseliny polymethakrylové; lipasa; Fungal Proteins; Lipase; Saccharomyces cerevisiae; imobilizované buňky; chitosan; Chitosan; Polymethacrylic Acids; Enzymes, Immobilized; Immobilization; fungální proteiny; Magnetics; Magnetic fluid; Cells, Immobilized; magnetismus; Poly(methacrylic acid); Candida; enzymy imobilizované